Holland, Rebecca (Goldberg) (audio interview #3 of 3) - Holland, Rebecca (Goldberg) (b. 10/10/1896 - ); Prickett, Patti, interviewer
INTERVIEW DESCRIPTION - This third and final interview with Rebecca Holland Goldberg, conducted in her home as a part of a UCLA student project , is sometimes difficult to hear because of muffled sound. TOPICS - 1917 strike in Chicago; 1922 general strike in New York; and the politics, composition and role of the Women's Trade Union League;social values, including attitudes toward free love; Brookwood Labor College; and ILGWU in Los Angeles; 12/3/1974